ANALYSIS OF THE EFFECT OF MARKETING MIX PRODUCT PURCHASE DECISION ON HAND PHONE (Case Study on Hand Phone Users Nokia Students at the College of Economic Sciences Nusa Megarkencana) - Setyawan, Aris; Lastari, SE.,MM, Siwi; Murdo,M.Si, Drs. Yuri (Management, 2010)
At first handphone prices high enough so that the users cell phone is identical with the rich or the rich kid. But today along with the affordable price of mobile phone phenomenon, namely cell phones are no longer a luxury which only the upper class only, but will also owned by various parties, including students, civil servants, private sectors, even the children were already many use cell phones. With the emergence of various kinds of brand mobile phone easier than ever consumers in choosing the desired product to be purchased. The existence of competition between manufacturers of cellular phones raises the motivation for each producer to improve the performance of the company in mobile phone products that consumers demand. In marketing hand phone, one brand of mobile phone top brands dominate the market is Nokia. This is possible because the Nokia brand marketing mix very well. For example in terms of product mix, customers can choose according to their respective standard, for example, from the completeness of features, ease of operation, technological sophistication, and others. Keywords : marketing mix, product purchase decision